Parkinson’s disease: animal models and dopaminergic cell vulnerability - Blesa, Javier; Przedborski, Serge (Frontiers in Neuroanatomy, 2014)
Parkinson's disease (PD) is a neurodegenerative disorder that affects about 1.5% of the global population over 65 years of age. A hallmark feature of PD is the degeneration of the dopamine (DA) neurons in the substantia nigra pars compacta (SNc) and the consequent striatal DA deficiency. Yet, the pathogenesis of PD remains unclear. Despite tremendous growth in recent years in our knowledge of the molecular basis of PD and the molecular pathways of cell death, important questions remain, such as: 1) why are SNc cells especially vulnerable; 2) which mechanisms underlie progressive SNc cell loss; and 3) what do Lewy bodies or α-synuclein reveal about disease progression. Understanding the variable vulnerability of the dopaminergic neurons from the midbrain and the mechanisms whereby pathology becomes widespread are some of the primary objectives of research in PD. Animal models are the best tools to study the pathogenesis of PD. The identification of PD-related genes has led to the development of genetic PD models as an alternative to the classical toxin-based ones, but does the dopaminergic neuronal loss in actual animal models adequately recapitulate that of the human disease? The selection of a particular animal model is very important for the specific goals of the different experiments. In this review, we provide a summary of our current knowledge about the different in vivo models of PD that are used in relation to the vulnerability of the dopaminergic neurons in the midbrain in the pathogenesis of PD.